Clinical, Anatomical, and Densitometric Changes following Dresden vs. Accelerated Corneal Cross-Linking in Progressive Keratoconus - Prinz, Julia; Kuerten, David; Schellhase, Hannah; Koutsonas, Antonis; Djalali-Talab, Yassin; Walter, Peter; Fuest, Matthias (Klinische Monatsblätter für Augenheilkunde, 2024)
Background To compare clinical, anatomical, and densitometric changes following Dresden (DCXL) vs. accelerated (ACXL) corneal UVA cross-linking (CXL; Avedro KXL, Geuder, Heidelberg, Germany) in progressive keratoconus (KC).Methods and Material In this retrospective study, we analyzed 20 patients following DCXL (3 mW/cm², 30 min, 5.4 J/cm²) and 44 patients following ACXL (9 mW/cm², 10 min, 5.4 J/cm²) between January 2016 and February 2020. Uncorrected visual acuity (UCVA), best spectacle-corrected visual acuity (BSCVA), central corneal thickness (CCT), steepest keratometry (Kmax), keratoconus index (KI), thinnest pachymetry (Pthin), and corneal densitometry (CD) were measured before and 3, 6, 12, and 24 months after CXL.Results During the follow-up period, no changes in UCVA, BSCVA, Kmax, KI, or Pthin occurred. CCT significantly decreased 3 months after DCXL (p = 0.032) and ACXL (p = 0.006). At the 12- and 24-month follow-up, CCT remained decreased in the DCXL (p = 0.035, 0.036, respectively) but not in the ACXL group. At the 12-month follow-up, the reduction in CCT was significantly greater in DCXL compared to ACXL (p = 0.012). At the 3-, 6-, 12-, and 24-month follow-ups, we found a significant increase in the anterior stroma CD following DCXL (p = 0.019, 0.026, 0.049, 0.047, respectively) but not ACXL. The CD changes were localized in the central concentric zones (0.0 to 6.0 mm). No intra- or postoperative complications occurred.Conclusion ACXL and DCXL effectively halted KC progression. ACXL proved to be a safe time-saving alternative to conventional DCXL. DCXL led to a reduction in CCT and an increment in the CD of the central anterior stroma during 24 months of follow-up.
Keywords: keratoconus; cornea; Dresden protocol; accelerated protocol